2020
DOI: 10.3390/toxins12120793
|View full text |Cite
|
Sign up to set email alerts
|

Boronic Acids of Pharmaceutical Importance Affect the Growth and Photosynthetic Apparatus of Cyanobacteria in a Dose-Dependent Manner

Abstract: The dynamic increase in the commercial application of antimicrobial derivatives of boronic acids, and potential impact of their presence in aquatic systems, supports the necessity to study the toxicity of these substances towards microorganisms of crucial meaning in the environment. One example of the mentioned derivatives is tavaborole (5-fluoro-substituted benzoxaborole), a pharmaceutical agent with antifungal activity. Cyanobacteria were used as model organisms, which are photoautotrophic prokaryotes, as re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…The influence of Tavaborole, as well as other benzoxaboroles, on the growth and composition of photosynthetic pigments in cyanobacteria ( Chroococcidiopsis thermalis, Arthrospira platensis, A. fusiformis, A. maxima and Anabaena ) was also investigated. It was shown that the investigated compounds changed the quantitative relationships between the contents of chlorophylls, phycobiliproteins and carotenoids within those microorganisms [ 86 ]. A mechanochemical method of fluorinated bis(benzoxaboroles) synthesis was recently developed [ 70 ].…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…The influence of Tavaborole, as well as other benzoxaboroles, on the growth and composition of photosynthetic pigments in cyanobacteria ( Chroococcidiopsis thermalis, Arthrospira platensis, A. fusiformis, A. maxima and Anabaena ) was also investigated. It was shown that the investigated compounds changed the quantitative relationships between the contents of chlorophylls, phycobiliproteins and carotenoids within those microorganisms [ 86 ]. A mechanochemical method of fluorinated bis(benzoxaboroles) synthesis was recently developed [ 70 ].…”
Section: Antimicrobial Activitymentioning
confidence: 99%